Dynamic deformation behavior and corresponding constitutive model of ultra-high strength DP1000 steel. (April 2022) - Hui, Li; Rui, Feng
Abstract: The static and dynamic mechanical properties of DP1000 steel were tested using an electronic universal testing machine controlled by a microcomputer at the strain rates of 10 −4 –10 −2  s −1 and a high speed tensile testing machine at the strain rates of 10 −1 –10 3  s −1 . The effect of strain rates on the stress-strain curves and the work hardening rate were obtained and analyzed. The modified dynamic Johnson-Cook model was established to characterize the dynamic deformation behavior. The dynamic compression characteristics and energy absorption law of thin-walled beam of DP1000 steel were determined by testing and using the Abaqus finite element simulation on account of the modified dynamic Johnson-Cook model (shortly the J-C model) to verify that the predicted values are in good agreement with the experimental ones. Highlights: Mechanical deformation behavior, instability and fracture mechanism under high strain rate. Establishment of dynamic constitutive model. Test on the dynamic impact properties. Simulation of dynamic impact property based on Abaqus software introducing established dynamic model.